ANALISIS PENERAPAN ELEKTRONIK PAJAK BUMI DAN BANGUNAN (E-PBB) (STUDI PADA DINAS PENDAPATAN DAERAH KABUPATEN LAMONGAN) - Hidayat, Kadarisman; Dewantara, Rizki Yudhi; Husnia, Fitria Nur (Jurnal Mahasiswa Perpajakan, 2016)
Electronic Tax Property (E-PBB) is application which uses to conduct the management tax property sector rural and urban areas in Lamongan. PBB-P2 management through the application of E-PBB consisting of data collection, judgment, determination, billing, payment and one door service. The implementation of E-PBB  in Lamongan was already carried out well, but there needs to be active cooperation from tax payers to help tax management by using E-PBB. Participation tax payers in the management of PBB-P2 consisting of the delivery of notification letters of tax object (SPOP) and the payment of PBB-P2. E-PBB is one part of the implementation of e-government program has already been held by Lamongan. E-Government is public service provided to the public through the use of technology and information in order to increase the quality of public services. There are 8 element success of the project e-government, political environment, leadership, planning, stakeholders, transparency, budgets, technology and innovation. E-PBB have met 8 elements success e-government project, but there were 1 element is not yet optimal, the element  is stakeholder. Comprising the government of stakeholders, private and tax payers, stakeholders taxpayers still working on optimal because low socialization and knowledge of application. Keywords: PBB-P2,  E-PBB, E-Government ABSTRAK E-PBB aplikasi pengelolaan PBB-P2 di Kabupaten Lamongan. Pengelolaan PBB-P2 melalui aplikasi E-PBB terdiri dari pendataan, penagihan, penetapan, penilaian, pembayaran dan pelayanan PBB-P2. Penerapan E-PBB di Kabupaten Lamongan sudah dilaksanakan dengan baik, hanya masih diperlukan kerjasama aktif wajib pajak PBB-P2 untuk mensukseskan pengelolaan pajak melalui aplikasi E-PBB dengan menyampaikan Surat Pemberitahuan Objek Pajak (SPOP) dan pembayaran PBB-P2 yang terhutang. E-PBB merupakan salah satu bentuk pelaksanaan E-Government yang telah dilaksanakan oleh Pemerintah Kabupaten Lamongan. E-Government merupakan pelayanan publik yang diberikan kepada masyarakat melalui penggunaan teknologi dan informasi guna meningkatkan kualitas pelayanan publik. Delapan (8) elemen sukses pelaksanaan proyek E-Government, yaitu political environment, leadership, planning, stakeholders, transparency/visibility, budgets, technology dan innovation. E-PBB telah memenuhi 8 elemen kesuksesan proyek E-Government, namun terdapat 1 (satu) elemen yang masih belum optimal yaitu stakeholders. Stakeholders terdiri  dari pemerintah, pihak swasta dan wajib pajak, stakeholder wajib pajak masih berjalan dengan optimal dikarenakan sosialisasi yang rendah dan pengetahuan tentang aplikasi E-PBB juga rendah. Kata Kunci: PBB-P2, E-PBB, E-Government